Historical Incidences of Credit Rationing among Micro and Small Enterprises in Kenya - Mugambi, Kenneth Majau; A van der Merwe, Alex (International Journal of Economics and Financial Issues, 2017)
In the mid-2000s, the Government of Kenya recognised the existence of institutional barriers preventing micro and small enterprises (MSEs) from directly accessing credit from financial institutions. This development informed the change of lending policy from direct lending to group lending in government supported programmes. However, this change was effected without a comprehensive theoretical and empirical examination of the underlying reasons why MSEs failed to access credit. This study fills this gap by investigating the the underlying reasons MSEs were credit rationed in Kenya. The general consensus from this study is that there was a high incidence of credit rationing in Kenya in 1990s and 2000s which stemmed from information asymmetry. The study concludes that the Government’s current policy of promoting group lending is indeed workable if the mode can assist in mitigating information asymmetry in credit markets. Keywords: Credit rationing information asymmetry, Micro and small enterprises. JEL: Classifications: D5, D8